A Study of Academic and Infrastructural Input and Achievement of Scheduled Caste Students of Residential Schools of Madhya Pradesh - Pillai, Dr. Anil Kumar MB (INDIAN EDUCATIONAL REVIEW, 2013)
The study is an attempt to examine infrastructural and academic inputs being provided and the outcome of schooling in terms of achievement of scheduled caste students of Residential Schools of Madhya Pradesh. The findings of the study depicts that there are acute deficiency of infrastructural facilities in Residential Schools during the study period. Achievement of students in subjects like Physics, Chemistry, Mathematics and General English is not satisfactory. There is a need to create congenial environment to promote learning in the campus of Residential Schools. The levels of achievement of learners are increasing in these institutions, thus the Government should continue the scheme of Residential Schools for scheduled castes and it must be further strengthened.